The Associative Characteristics of Linguophilosophical Concept “Freedom” in English, Armenian and Chinese Linguocultures - Grigoryan, Gevorg; Ren, Wenxuan; Ning, Huichun (Տիգրան Մեծ)
The article entitled “The Associative Characteristics of Linguophilosophical Concept “Freedom” in English, Armenian and Chinese Linguocultures” is devoted to the study of the linguophilosophical concept “Freedom” in different linguocultures, which is deeply related to the formationof the meaning of life for any individual and the main axiological functions of personality. The aim of the studyis to give a complete characteristic of the linguophilosophical concept “Freedom” in the above mentioned linguocultures. The novelty of this workis determined by representing the construction of the model of “freedom” as a linguophilosophical concept, as well as defining its philosophical, cultural, linguistic and associative characteristics. This study is also important in identifying the ways of expressing “Freedom” in the lexical-phraseological system of language and communicative behavior.
Keywords: Philosophy of language; Literature